2015
DOI: 10.1002/ajh.24188
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic parameters and RBC alloimmunization in children with sickle cell disease on chronic transfusion

Abstract: Alloimmunization against red blood cell (RBC) antigens is a cause of morbidity and mortality in transfused patients with sickle cell disease (SCD). To investigate distinguishing characteristics of patients who develop RBC alloantibodies after transfusion (responders) versus those who do not (non-responders), a crosssectional study of 90 children with SCD on chronic RBC transfusion therapy at a single institution was conducted in which 18 immune parameters (including T and B cell subsets) were tested via flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
64
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 75 publications
9
64
1
5
Order By: Relevance
“…Recently, Ryder et al (2016) reported that 16% of primarily male alloimmunized patients treated at a Veterans Administration hospital had a chronic autoimmune disorder, compared to 8% of nonalloimmunized patients. Multiple studies have also described a close association between RBC alloantibodies and RBC autoantibodies (Dhawan et al, 2014;Nickel et al, 2015). Animal studies (Gibb et al, 2017a,b) suggest that a potential unifying hypothesis for the connection between some types of autoimmunity (Crow, 2014) and alloimmunization may involve type 1 interferon signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ryder et al (2016) reported that 16% of primarily male alloimmunized patients treated at a Veterans Administration hospital had a chronic autoimmune disorder, compared to 8% of nonalloimmunized patients. Multiple studies have also described a close association between RBC alloantibodies and RBC autoantibodies (Dhawan et al, 2014;Nickel et al, 2015). Animal studies (Gibb et al, 2017a,b) suggest that a potential unifying hypothesis for the connection between some types of autoimmunity (Crow, 2014) and alloimmunization may involve type 1 interferon signalling.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Contrasting these animal studies, some observational studies in thalassemia patients suggested splenectomy to be associated with increased red cell alloimmunization, 4,5 while others did not find any association. 6,7 In the study herein, we assessed the association between the anatomic absence of the spleen and (transfusion-related) red cell alloantibody induction in our multicenter case-control Risk Factors for Alloimmunization to Red Blood Cell Transfusion (R-FACT) study cohort. This cohort includes 505 alloimmunized cases and 1,010 non-alloimmunized matched controls among a primarily Caucasian source population of 24,063 patients receiving their first and subsequent red cell transfusions between January 2005 and December 2013 at one of six participating hospitals in the Netherlands, as described earlier.…”
mentioning
confidence: 99%
“…Patients in the transfused group had received a median of 93 RBC units (range, 6-543 units); additional details about this group have been previously reported. 22 The prevalence of antibodies in the transfused versus never transfused groups was not significantly different for any of the studied platelet glycoprotein antigens ( Table 1). The standardized OD values for each platelet glycoprotein antigen also were not significantly different for the transfused versus never transfused groups (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Patients in the transfused group were more likely to have undergone splenectomy (27% vs. 0%; p = 0.004) and were less likely to be receiving hydroxyurea (8% vs. 46%; p < 0.0001). Patients in the transfused group had received a median of 93 RBC units (range, 6‐543 units); additional details about this group have been previously reported …”
Section: Resultsmentioning
confidence: 99%